Azotriptycenes: Photoswitchable Molecular Brakes - Stockerl, Willibald J.; Reißenweber, Lilli; Gerwien, Aaron; Bach, Nicolai; Thumser, Stefan; Mayer, Peter; Gschwind, Ruth M.; Dube, Henry (Chemistry - A European Journal, 2023)
The control of molecular motions is a central topic of molecular machine research. Molecular brakes are fundamental building blocks towards such goal as they allow deliberately decelerating specific motions after an outside stimulus is applied. Here we present azotriptycenes as structural framework for light-controlled molecular brakes. The intrinsic kinetics and their changes upon azotriptycene isomerization are scrutinized comprehensively by a mixed theoretical and variable temperature NMR approach. With azotriptycenes C−N bond rotation rates can be decelerated or accelerated reversibly by up to five orders of magnitude. Rate change effects are highly localized and are strongest for the C−N bond connecting a triptycene rotor fragment to the central diazo group. The detailed mechanistic insights provide a solid basis for further conscious design and applications in the future.
CRIS-Team Scopus Importer:2023-12-15

Directionality Reversal and Shift of Rotational Axis in a Hemithioindigo Macrocyclic Molecular Motor - Reißenweber, Lilli; Uhl, Edgar; Hampel, Frank; Mayer, Peter; Dube, Henry (Journal of the American Chemical Society, 2024)
Molecular motors are central driving units for nanomachinery, and control of their directional motions is of fundamental importance for their functions. Light-driven variants use easy to provide, easy to dose, and waste-free fuel with high energy content, making them particularly interesting for applications. Typically, light-driven molecular motors work via rotations around dedicated chemical bonds where the directionality of the rotation is dictated by the steric effects of asymmetry in close vicinity to the rotation axis. In this work, we show how unidirectional rotation around a virtual axis can be realized by reprogramming a molecular motor. To this end, a classical light-driven motor is restricted by macrocyclization, and its intrinsic directional rotation is transformed into a directional rotation of the macrocyclic chain in the opposite direction. Further, solvent polarity changes allow to toggle the function of this molecular machine between a directional motor and a nondirectional photoswitch. In this way, a new concept for the design of molecular motors is delivered together with elaborate control over their motions and functions by simple solvent changes. The possibility of sensing the environmental polarity and correspondingly adjusting the directionality of motions opens up a next level of control and responsiveness to light-driven nanoscopic motors.
CRIS-Team Scopus Importer:2024-08-16